MANAJEMEN NUTRISI PADA IBU HAMIL TM II DENGAN KEKURANGAN ENERGI KERONIK DI PMB “E” KOTA BENGKULU - Herlinda Herlinda; Iin Nilawati; Eka Septiani (Mitra Raflesia (Journal of Health Science), 2023)
Background: Comprehensive midwifery care is midwifery care on an ongoing basis from pregnancy to family planning as an effort to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Pregnancy is a unique natural condition because during pregnancy the mother will experience changes in anatomy and physiology. The care provided aims to help monitor and detect possible complications that accompany the mother and baby.Method: This type of research is descriptive with a case study method. In Mrs. R, G2P1A0 18 weeks pregnant with KEK with lila 23 cm, will be given comprehensive care with Nutrition Management.Results: The results of the care given to Mrs. R during pregnancy was Mrs, R had visited 6 times, the quality of ANC services obtained met the 10 T standard. In the second trimester of SEZ pregnancy, complementary midwifery care was provided, namely Nutrition Management. Finally, the mother's weight increased and Lila increased to 23.7 cm, which means she experienced an increase of 0.7 cm.Conclusion: From the results of the care provided, it can be concluded that the nutritional management given to Mrs. R has an effect on the incidence of SEZ on Mrs. R